Implikasi Pencegahan Dumping Sebagai Unfair Trade Practices Terhadap Negara Berkembang - Trisnawati, Eunike; Farisi, Mochammad; Pebrianto, Doni Yusra (Uti Possidetis: Journal of International Law, 2020)
Abstract Dumping is a trade activity by the exporter do by selling commodity in international markets at a price less than normal value or under than commodity price in the importer countries. until this cause problem as unfair trade practices. Some dumping prevention polices born to protect domestic market from unfair trade practices. However that polices often misused, not uncommon developed countries doing the protection for their domestic industry. In trade who abused can trigger unfairÂ  trade practices. This type of research is normative juridical. This studyÂ  discusses and analyze how impact of application Article VI of Agreement on tariff and trade in preventing dumping dictionary, dumping in value as unfair trade practices, but in reality Anti-dumping and protectionism practice towards developing countries shows that application of anti-dumping duties and protectionism need to be given special attention and must match with procedures contained in Anti-dumping code. This has purpose to reduce protection measures which can be harmful to other countries who do export activities especially developing countries. World organization need towatch over trade activities against all forms resistance who created unfair trade practices by considering policies which already existed.